The Role Of Islamic Capital Market In Developing Muslim Economy - Abd Jalil, Borham; Muhammad Azizur Rahman, Ramli; Mohd Firdaus, Shahidin (2014)
The role Islamic capital market is to raise funds, trading and mobilizing funds from one sector to another sector of the economy to ensure the humankind life. Unlike the conventional capital market it objectives is maximization of profit. Islamic capital market has two objectives; firstly is to eliminate usury and secondly to develop Islamic economics and the global economy. These two objectives should be the role of Islamic Capital Market in developing muslim economy. The Islamic capital market comprises two main components: the debt market and the equity market. Sukuk, known as Islamic bonds, have been the most active Islamic debt Market. Nevertheless it is active but the objective of the Islamic social development must be complying. It’s not just to boost the rich corporate economy but its role has to be helping muslim community to develop their economy power. This paper discusses the relationship between Islamic Capital Market and Maqasid. Also discuss its roles in developing real estate industry and halal industry. Many scholars agree that innovation in Islamic capital market must be actively discuss as the Islamic capital market broadly use in term of development of Muslim economy.